Beta-Alanine supplementation reduces acidosis but not oxygen uptake response during high-intensity cycling exercise - Baguet, A.; Koppo, K.; Pottier, A.; Derave, W. (European Journal of Applied Physiology, 2010)
The oral ingestion of beta-alanine, the rate-limiting precursor in carnosine synthesis, has been shown to elevate the muscle carnosine content. Carnosine is thought to act as a physiologically relevant pH buffer during exercise but direct evidence is lacking. Acidosis has been hypothesised to influence oxygen uptake kinetics during high-intensity exercise. The present study aimed to investigate whether oral beta-alanine supplementation could reduce acidosis during high-intensity cycling and thereby affect oxygen uptake kinetics. 14 male physical education students participated in this placebo-controlled, double-blind study. Subjects were supplemented orally for 4 weeks with 4.8 g/day placebo or beta-alanine. Before and after supplementation, subjects performed a 6-min cycling exercise bout at an intensity of 50% of the difference between ventilatory threshold (VT) and VO(2peak). Capillary blood samples were taken for determination of pH, lactate, bicarbonate and base excess, and pulmonary oxygen uptake kinetics were determined with a bi-exponential model fitted to the averaged breath-by-breath data of three repetitions. Exercise-induced acidosis was significantly reduced following beta-alanine supplementation compared to placebo, without affecting blood lactate and bicarbonate concentrations. The time delay of the fast component (Td(1)) of the oxygen uptake kinetics was significantly reduced following beta-alanine supplementation compared to placebo, although this did not reduce oxygen deficit. The parameters of the slow component did not differ between groups. These results indicate that chronic beta-alanine supplementation, which presumably increased muscle carnosine content, can attenuate the fall in blood pH during high-intensity exercise. This may contribute to the ergogenic effect of the supplement found in some exercise modes.